Determinants of Auditor's Ability to Detect Fraud: Internal and External Factors - Rizkiana Iskandar; Muh. Syahru Ramadhan; M. Ikhwan Mansyuri; Rizky Ramadhan (Publisher Cv. Inara, 2022)
Fraud cases that occur in Indonesia have fluctuated every year and in 2020 the number of state losses due to fraud is the largest in the last five years. The purpose of this study was to determine the effect of internal factors (experience and professional skepticism) and external (whistleblowing and time budget pressure) on the ability of auditors to detect fraud. Sampling using a survey method in the form of a questionnaire given to respondents, namely internal auditors the inspectorate and produced as many as 55 samples. Data testing was carried out by multiple regression testing using the SPSS version 23 program. The results showed that internal factors consisting of experience and professional skepticism and external factors, namely whistleblowing, had a positive effect on the ability of auditors to detect fraud. Meanwhile, time budget pressure does not prove to have an effect on auditors' ability to detect fraud.